Uterine Rupture : A Catastrophic Complication - Jehan Ara , Kaukab Naheed , Farzana Kazmi , Shagufta Saeed Sial (Journal of Rawalpindi Medical College, 2010)
Background: Lack of antenatal care , injudicious use of oxytocin/prostaglandins , delivery by unskilled birth attendants and caesarean sections in previous pregnancies can lead to rupture uterus Methods: In this Prospective observational study, 30 cases of uterine rupture were included. Risk factors, clinical presentations, operative findings and post operative complications were recorded. Results: The incidence of uterine rupture was 0.24% in present study. Most of the patients were nonbooked (86.7%), and came from rural area (76.7%). Common risk factors for uterine rupture were women with previous caesarean sections (86.7%), injudicious use of oxytocin and prostaglandins (33.3%), labour supervised by unskilled birth attendant (86.7%), trial of labour conducted outside the hospital (93.3), grandmultipara(16.7%) and prolonged obstructed labour(23.3%). Shock (36.7%) and sudden loss of uterine contractions (33.3%) were the commonest presentations. Lower uterine segment was involved in 83.3% cases. Repair of the uterus was possible in 80 % cases.Peripartum hysterectomy was done in 20 % cases. Blood transfusion was required in all the cases (100%) and fresh frozen plasma in 50%cases. .There was no maternal death. There were 28 cases of stillbirths, 26 fresh and 2 macerated. Only 2 fetuses were born alive out of which 1 died within 24 hour contributing to perinatal mortality of 933.3per 1000 live births. Conclusion: Injudicious use of Oxytocin/prostaglandin, history of previous caesarean section and labour supervised by unskilled birth attendants can increase the risk of uterine rupture .